2003
DOI: 10.1016/s0022-2836(02)01369-4
|View full text |Cite
|
Sign up to set email alerts
|

Cis-acting Regulatory Elements in the Potato Virus X 3′ Non-translated Region Differentially Affect Minus-strand and Plus-strand RNA Accumulation

Abstract: The 72nt 3' non-translated region (NTR) of potato virus X (PVX) RNA is identical in all sequenced PVX strains and contains sequences that are conserved among all potexviruses. Computer folding of the 3' NTR sequence predicted three stem-loop structures (SL1, SL2, and SL3 in the 3' to 5' direction), which generally were supported by solution structure analyses. The importance of these sequence and/or structural elements to PVX RNA accumulation was further analyzed by inoculation of Nicotiana tabacum (NT-1) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 89 publications
2
36
0
Order By: Relevance
“…Because minus‐strand synthesis initiates from the 3′‐terminus of the genome, it is likely that sequences and/or structures in the 3′‐region are required for template recognition by the viral replicase complex and for the initiation of RNA synthesis. All PVX strains sequenced to date have identical sequences in the 74 nt 3′‐NTR (Pillai‐Nair et al ., 2003), suggesting that the sequence in this region is important for virus viability. Analyses of computer‐predicted structures and solution structural probing indicate that the PVX 3′‐NTR can fold into three stem‐loop structures, but the formation of only one (SL3; Fig.…”
Section: Requirements For Cis‐acting Rna Elementsmentioning
confidence: 99%
“…Because minus‐strand synthesis initiates from the 3′‐terminus of the genome, it is likely that sequences and/or structures in the 3′‐region are required for template recognition by the viral replicase complex and for the initiation of RNA synthesis. All PVX strains sequenced to date have identical sequences in the 74 nt 3′‐NTR (Pillai‐Nair et al ., 2003), suggesting that the sequence in this region is important for virus viability. Analyses of computer‐predicted structures and solution structural probing indicate that the PVX 3′‐NTR can fold into three stem‐loop structures, but the formation of only one (SL3; Fig.…”
Section: Requirements For Cis‐acting Rna Elementsmentioning
confidence: 99%
“…Several viral and cellular mRNAs contain a short U-rich region upstream of the poly(A) signal. This sequence recruits accessory proteins, such as hFip1, PTB, Hu family proteins, cleavage and polyadenylation specificity factor components, and U2AF 65 , which facilitate polyadenylation and complete the formation of the mRNA 3Ј end (1,11,17,21,23,35,52). In addition, the U-rich region of the myosin phosphatase targeting subunit 1 pre-mRNA has been shown to mediate an alternative splicing event by interacting with either T-cell intracellular antigen 1 or PTB during tissue-specific developmental regulation (37).…”
mentioning
confidence: 99%
“…By conducting EMSA, UV cross-linking, and yeast three-hybrid analyses, we identified those sequences and/or regions of the PVX SL1(+) RNA that are required for CP binding. The SL structures at the 5' end of the positive-strand RNA of the genomes contain at least three well-defined stem-loop structures (SL1, SL2, and SL3 in the 3' to 5' direction) and are well conserved in most reported potexviruses (Chen et al, 2010;Miller et al, 1998;Pillai-Nair et al, 2003). In this regard, it is worth noting that SL1(+) structures are identical in all sequenced PVX strains.…”
mentioning
confidence: 93%
“…Previous studies have indicated that the 5' and 3'-terminal nt of the PVX genome can form conserved SL structures (Miller et al, 1998;Pillai-Nair et al, 2003). The SL structure formed by the 5'-terminal nt containing the ACrich single-stranded region and the SL1 secondary structure is more stable than that formed by the 3'-terminal nt.…”
mentioning
confidence: 96%